Climate Change, Moral Integrity, and Obligations to Reduce Individual Greenhouse Gas Emissions. Issue 1 (2nd January 2018) - Hedberg, Trevor
Abstract: Environmental ethicists have not reached a consensus about whether or not individuals who contribute to climate change have a moral obligation to reduce their personal greenhouse gas emissions. In this paper, I side with those who think that such individuals do have such an obligation by appealing to the concept of integrity. I argue that adopting a political commitment to work toward a collective solution to climate change—a commitment we all ought to share—requires also adopting a personal commitment to reduce one's emissions. On these grounds, individuals who contribute to climate change have a prima facie moral duty to lower their personal greenhouse gas emissions. After presenting this argument and supporting each of its premises, I defend it from two major lines of objection: skepticism about integrity's status as a virtue and concerns that the resulting moral duty would be too demanding to be morally required. I then consider the role that an appeal to integrity could play in galvanizing the American public to take personal and political action regarding climate change.